Different Strokes in Boundary Artistry: Commentary on Cooper's "Blurring Boundaries or Why Do We Refer to Sexual Misconduct With Patients as 'Boundary Violation'". Issue 2 (3rd March 2016) - Celenza, Andrea
Abstract : In this commentary, the useful idea of psychoanalytic process as boundary art is taken up, elaborated, and further conceptualized. Two registers of psychic experience are utilized: the mutual and asymmetric modes of relating inherent in and definitional of analytic process. In line with Steven H. Cooper's ideas, the givenness of boundaries in the mutual realm constitute the psychic matter of self-other differentiation. In contrast, the asymmetrical register marks boundaries as asserted and intended to be actualized in behavior. The usefulness of "boundary violation" as an expression of a perversion of ethical commitments is construed as a justified and necessary phrase. Boundaries in the asymmetrical register, continually asserted, make play and flex in the mutual register possible and in this way form a dialectical relation. In concert with Cooper, these assertions reflect the power of boundaries to 'allow us to get lost.' Fallibilities in the ways theories can be coopted to erase (and thereby truncate) aspects of the psychoanalytic process are described as a misuse (violation?) of boundary art.